Worldwide distribution and theoretical spreading of Trichoferus campestris (Coleoptera: Cerambycidae) depending on the main climatic elements. Issue 3 (12th August 2019) - Keszthelyi, Sándor; Fehér, Balázs; Somfalvi‐Tóth, Katalin
Abstract: The velvet longhorned beetle, Trichoferus campestris (Coleoptera: Cerambycidae) is a serious wood‐boring pest that is a major threat to the phytosanitary condition of forests and orchards. Its worldwide expansion is a major concern for plant health. We have collected all bibliographical references, phytosanitary reports and authentic photographic evidence from entomological websites to determine the worldwide distribution of T. campestris . The theoretical directions of the spreading and actually occupied area of this arthropod pest were determined over the whole Holarctic range. Furthermore, the potential distribution area was calculated using cumulated temperature in the growing season averaged over 15 years both in the Palearctic and Nearctic regions. Holarctic expansion of the species, including the main parts of North America and Eurasia, is clearly indicated. Its populations occur in 29 countries to date, supported by documentation from 64 publications and 30 online forums. Its spread is continuously westward in the Palearctic; in the Nearctic, the spread was first southward from the Great Lakes region then eastward from Utah. The species has excellently adapted to circumstances of freight by ship and plane, as wood is often used, ensuring optimal conditions for the pest. In addition, the active spreading achieved by flying is an important factor contributing to its expansion. The primary criterion for controlling the species would be the introduction of a monitoring system in affected and exposed areas. Abstract : The expansion of velvet longhorned beetle, Trichoferus campestris (Faldermann, 1835) (Coleoptera: Cerambycidae) is a major concern for plant health. We have collected all bibliographical references, phytosanitary reports, and authentic photographic evidence from entomological websites to determine the worldwide distribution of this serious pest. Holarctic expansion, including the main parts of North America and Eurasia, of the species is clearly demonstrated. Spreading is continuously westward in the Palearctic, as well as southward from the Great Lakes region and eastward from Utah in Nearctic regions, as a function of its abiotic conditions.